2020
DOI: 10.3390/polym12020475
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Porous Recycled HDPE Biocomposites Foam: Effect of Rice Husk Filler Contents and Surface Treatments on the Mechanical Properties

Abstract: In this study, a biodegradable, cheap and durable recycled high-density polyethylene (rHDPE) polymer reinforced with rice husk (RH) fibre was fabricated into a foam structure through several processes, including extrusion, internal mixing and hot pressing. The effect of filler loading on the properties of the foam and the influence of RH surface treatments on the filler–matrix adhesion and mechanical properties of the composite foam were investigated. The morphological examination shows that 50 wt.% filler con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Generally, modulus and tensile strength would be improved with an increase in loading content of reinforcing fillers. The smaller fillers and better distribution/dispersion of fillers in composite matrix are also favored for mechanical enhancement [ 32 ]. It was reported that fillers with smaller size, specifically at the nanoscale, showed a better efficiency in improving modulus and tensile strength than those with a larger size, i.e., at the microscale [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, modulus and tensile strength would be improved with an increase in loading content of reinforcing fillers. The smaller fillers and better distribution/dispersion of fillers in composite matrix are also favored for mechanical enhancement [ 32 ]. It was reported that fillers with smaller size, specifically at the nanoscale, showed a better efficiency in improving modulus and tensile strength than those with a larger size, i.e., at the microscale [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have also reported the effect of fiber surface treatments on the water absorption of NF composites. 2,3,6,19,2123,28,29,36…”
Section: Resultsmentioning
confidence: 99%
“…For example, the selection of the polymers—based on their chain length and molecular weight, functional groups and species, and so on)—and how the polymer chains interact with each other will have a notable impact on the morphologies and properties of the foams produced. For instance, in wood and plant stems, other natural functionally graded foam structures, the complex self-assembly and interaction of various polymer species (cellulose, hemicellulose, lignin, pectin, and so on) lead to a beautiful hierarchical cellular structure, making it a model functionally graded material [ 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Indeed, the minute changes in the polymer species, and their interactions and formations, lead to a wide variety of wood species in nature with a range of functional properties, including densities, strengths, and hardness [ 93 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ].…”
Section: Conclusion and Future Research Outlookmentioning
confidence: 99%